Striatal astrocytes transdifferentiate into functional mature neurons following ischemic brain injury - Duan, Chun‐Ling (Glia, 2015)
To determine whether reactive astrocytes stimulated by brain injury can transdifferentiate into functional new neurons, we labeled these cells by injecting a glial fibrillary acidic protein (GFAP) targeted enhanced green fluorescence protein plasmid (pGfa2‐eGFP plasmid) into the striatum of adult rats immediately following a transient middle cerebral artery occlusion (MCAO) and performed immunolabeling with specific neuronal markers to trace the neural fates of eGFP‐expressing (GFP(+)) reactive astrocytes. The results showed that a portion of striatal GFP(+) astrocytes could transdifferentiate into immature neurons at 1 week after MCAO and mature neurons at 2 weeks as determined by double staining GFP‐expressing cells with βIII‐tubulin (GFP(+)‐Tuj‐1(+)) and microtubule associated protein‐2 (GFP(+)‐MAP‐2(+)), respectively. GFP(+) neurons further expressed choline acetyltransferase, glutamic acid decarboxylase, dopamine receptor D2‐like family proteins, and the N‐methyl‐d‐aspartate receptor subunit R2, indicating that astrocyte‐derived neurons could develop into cholinergic or GABAergic neurons and express dopamine and glutamate receptors on their membranes. Electron microscopy analysis indicated that GFP(+) neurons could form synapses with other neurons at 13 weeks after MCAO. Electrophysiological recordings revealed that action potentials and active postsynaptic currents could be recorded in the neuron‐like GFP(+) cells but not in the astrocyte‐like GFP(+) cells, demonstrating that new GFP(+) neurons possessed the capacity to fire action potentials and receive synaptic inputs. These results demonstrated that striatal astrocyte‐derived new neurons participate in the rebuilding of functional neural networks, a fundamental basis for brain repair after injury. These results may lead to new therapeutic strategies for enhancing brain repair after ischemic stroke. GLIA 2015;63:1660–1670